Evaluation of the Relevance and Effectiveness of the C Level Equivalency Education for Productive Age Learners - Liza Tri Easti Putri; Sudarwan Danim; Muhammad Kristiawan (Journal of Social Work and Science Education, 2026)
In Indonesia, a significant portion of the productive-age population lacks formal secondary education credentials, limiting their employment and further education opportunities. This study employed a qualitative goal-oriented evaluation (Tyler, 1949) to assess the relevance and effectiveness of the C Level Equivalency Program at PKBM Putri Raflesia, using interviews, observations, and document analysis. Findings indicate that the program’s objectives are highly relevant to learners’ needs for diplomas and skills. The flexible, andragogical approach was effective in improving comprehension and participation, leading to significant impacts on graduates’ self-confidence, employment, and educational mobility. The study concludes that the C Level program is a vital mechanism for socio-economic empowerment, demonstrating that program success hinges more on pedagogical strategies and relevance than on material resources. This research contributes by highlighting the role of community-based non-formal education in addressing educational inequality, providing practical insights for policymakers to strengthen adult learning programs, and offering novelty in applying Tyler’s model to evaluate non-formal education for productive-age learners in Indonesia.